2021
DOI: 10.3390/agriculture11010054
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Input and Output Linkages in Agricultural Production Systems

Abstract: This paper conducts a comprehensive analysis of the agricultural sector’s resource allocation and production decisions. This paper uses the differential systems with quasi-fixity to evaluate the complete agricultural production system, which examines the input and output linkages in terms of elasticities. The differential systems are estimated using the maximum likelihood estimation technique based on the two-step profit-maximizing procedure in theory. The results reveal that livestock production requires more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…iii) While the increase in input prices affects production negatively in the short run, it has a positive impact over the long run in Turkey. Suh & Moss (2021), Komarek et al (2017) and Srivastava (2017) concluded that input prices affect agricultural production negatively. On the other hand, Taylor & Koo (2008) emphasized that producers respond to the high input and commodity prices by increasing supply for compensating decrease in farm income.…”
Section: Conclusion and Policy Advicementioning
confidence: 99%
“…iii) While the increase in input prices affects production negatively in the short run, it has a positive impact over the long run in Turkey. Suh & Moss (2021), Komarek et al (2017) and Srivastava (2017) concluded that input prices affect agricultural production negatively. On the other hand, Taylor & Koo (2008) emphasized that producers respond to the high input and commodity prices by increasing supply for compensating decrease in farm income.…”
Section: Conclusion and Policy Advicementioning
confidence: 99%
“…Lower revenues through the food and hospitality sectors significantly contributed to the drop in worldwide agricultural product trading. During the outbreak, a recurring issue in several economies worldwide was the governmental encouragement of the food self-sufficiency concept (Hrybau et al, 2019;Suh & Moss, 2021). Several governments used trading limitations or other measures to replace domestically grown agricultural products in domestic consumption and commercial food production to promote self-sufficiency and reduce dependence on agricultural product imports.…”
Section: International Trade and Agricultural Products Movementsmentioning
confidence: 99%
“…First, land certification is an effective strategy for securing tenure, boosting farmer confidence in their land rights, and increasing land-related inputs and crop yield [ 19 ]. To put it another way, the impacts of secured ownership on loan availability and input incentives indicate that farmers without secure ownership will spend less on inputs and land improvements, employ fewer variable inputs, and produce less per unit of land [ 8 , 42 ]. Farmers only invest in land when they expect a steady return; therefore, they prefer to invest when their expectations are predictable [ 43 ].…”
Section: Theoretical Analysis and Hypothesismentioning
confidence: 99%
“…It has been mutually agreed that the efficiency of agricultural land can be promoted via the implementation of appropriate policies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. While vigorously increasing input in agricultural production [ 8 , 9 ], in the context of rapid urbanization development, the issue of how farmers’ restrictions regarding agricultural land can be loosened has been an important direction in rural land system reform in China [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%